A Life That Glorifies God Based on 1 Corinthians 6:19-20: A Study Theological About Life As the Temple of the Holy Spirit - Ritwan Imanuel Tarigan; Juni Balle (LPPM Universitas PGRI Sumatera Barat, 2025)
A life that glorifies God is calling main for every believer, as confirmed in 1 Corinthians 6:19–20 that body is the temple of the Holy Spirit and not owned by man alone, but rather belongs to God who has redeem with expensive price. Study This aim For analyze in a way theological meaning a life that glorifies God within context identity of believers as the temple of the Holy Spirit and the implications for life personal and community contemporary church. Approach used is theological-qualitative with method expositional and hermeneutic contextual, with source main text Bible as well as literature theological and academic. Results study show that, first, identity body as the temple of the Holy Spirit forms awareness existential that life of a believer fully is at in the authority of God. Second, glorifying God is not only expression worship liturgical, but covering all over dimensions life : spiritual, social, and ethical. Third, understanding This own implications theological and practical for church, especially in formation spirituality and testimony community faith in the midst modern secular and pluralistic society. Study This give contribution with expand understanding about body as the temple of the Holy Spirit perspective that is not only personal-moral, but Also communal-contextual, so that the life of a believer can become means statement the glory of God in holistic